Engineering active sites of two-dimensional MoS2 nanosheets for improving hydrogen evolution. Issue 11 (10th October 2016) - Kong, Xiangkai; Shen, Xiaochen; Zhang, Changlin; Oliaee, Shirin Norooz; Peng, Zhenmeng
Abstract : S edges were peeled off to disclose inner S as new under-coordinated atoms, which exposed more fresh active sites. Abstract : Generating more and fresh active sites is challenging for 2D MoS2 . Herein, the old S edges were peeled off and the inner S atoms were disclosed as under-coordinated atoms. This realized more and freshly active sites being exposed that facilitate adsorption of intermediates and lead to dramatic enhancements in its HER activity in both acid and alkaline electrolytes.